Julião Sarmento: the innuendo of the real - Amorim, João Pedro (2021)
Julião Sarmento’s body of work crosses multiple artistic disciplines and fields. The artist resorts to film and video as a means to reach the artistic expression of an idea, open to an infinitude of interpretations. This audiovisual essay looks at the way Julião Sarmento works with moving images, focusing in three main perspectives: the word, the (feminine) body and rhythm. We conclude that each one of Sarmento’s works builds a system of codes, of communication, that opens new understandings of the human relation with the ‘real’.